Proccedings of 10th International Conference "Environmental Engineering" 2017
DOI: 10.3846/enviro.2017.246
|View full text |Cite
|
Sign up to set email alerts
|

Concept of INS/GPS Integration Algorithm Designed for MEMS Based Navigation Platform

Abstract: Abstract. Nowadays, along with the advancement of technology one can notice the rapid development of various types of navigation systems. So far, the most popular satellite navigation, is now supported by positioning results calculated with the use of other measurement system. The method and manner of integration will depend directly on the destination of developed system. To increase the frequency of readings and improve the operation of outdoor navigation systems, one can support satellite navigation systems… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…As part of the latest research, the integrated navigation algorithm was implemented. Next, practical tests of the use of an algorithm integrated in car navigation were performed (Tomaszewski, 2017). Studies have shown that the applied solutions increase the accuracy, reliability and integrity of the navigation system.…”
Section: Integrated Multi-sensor Navigationmentioning
confidence: 99%
“…As part of the latest research, the integrated navigation algorithm was implemented. Next, practical tests of the use of an algorithm integrated in car navigation were performed (Tomaszewski, 2017). Studies have shown that the applied solutions increase the accuracy, reliability and integrity of the navigation system.…”
Section: Integrated Multi-sensor Navigationmentioning
confidence: 99%